African Higher Education System As Seen by a Researcher From Mozambique: Decolonization or Neocolonization? - YAKOVLEV Artem Igorevich (Ученые записки Института Африки Российской академии наук, 2025)
Review of the book: Uetela P.J. (2023). Higher Education and Decolonization in Africa. Cham: Palgrave Macmillan. https://doi.org/10.1007/978-3-031-38973-3